Pluralism in economics: its critiques and their lessons - Claudius Gräbner; Birte Strunk (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
This paper provides a taxonomy and evaluation of five common arguments against pluralism in economics: (1) the claim that economics is already pluralist, (2) the argument that if there was the need for greater plurality, it would emerge on its own, (3) the assertion that pluralism means "anything goes" and is thus unscientific, (4) the claim that economics must have a single core paradigm to justify its role as a major science, and (5) the contention that pluralism is an ideological movement from the left, and should not be granted scientific attention. We provide counter-arguments to all these arguments. Based on the assessment of these critiques we identify two main challenges to be faced by advocates of pluralism: first, the need to derive adequate quality criteria for a pluralist economics, and, second, the necessity to propose strategies that ensure the communication across different research paradigms. The paper concludes with some suggestions to meet these challenges.
Keywords: 330